Wawasan Al-Qur’an Tentang Pembelaan terhadap Kaum Tertindas: ‎Telaah atas Krisis Hak Asasi di Palestina - Wijaya, Muhammad Ikhsan; Abubakar, Ahmad; Mahfudz, Muhsin (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
This article examines the human rights crisis affecting the Palestinian people through a thematic interpretation of the concept of mustadh'afīn in the Qur'an. The prolonged conflict in Palestine, marked by military occupation, forced evictions, economic blockades, and attacks on civilians, has made the Palestinian people a concrete representation of the modern oppressed. The Qur'an pays special attention to the existence of the mustadh'afīn as a group that must be defended and empowered. Through an analysis of verses such as QS al-Nisa’ verse 75, QS al-Qasas verse 5, and QS al-Isra’ verses 4–7, this article shows that defending the oppressed is an essential teaching of Islam that stems directly from the values ​​of justice and human solidarity affirmed in the Qur’an. This study also highlights the moral responsibility of the international Muslim community to respond to the Palestinian crisis actively, systematically, and based on the values ​​of revelation. With an interdisciplinary approach between the study of interpretation, human rights, and geopolitical reality, this article emphasizes that defending the Palestinian people is not merely a moral demand, but also a sharia obligation based on the spirit of divine justice.